Recognized homonymous hemianopsia and delirium during the admission examination leading to diagnosis and appropriate treatment of a new stroke - Tsymbalov K; Fetkenhour D (Neuropsychiatric Disease and Treatment)
Konstantin S Tsymbalov, Douglas R Fetkenhour Department of Physical Medicine and Rehabilitation, University of Rochester Medical Center, Rochester, NY, USA Abstract: This case report describes the detection of homonymous hemianopsia and delirium during the admission physical examination of a patient with esophageal adenocarcinoma, resulting in the new diagnosis of subacute hemorrhagic stroke. The poststroke visual field defect can result in significant disability and reduction in quality of life. Patients with visual field cut show a severely reduced quality of life and require additional neuropsychological and visual rehabilitation. Only thorough physical examination is able to challenge prior negative positron emission tomography scan, leading to the diagnosis of subacute stroke and, following appropriate treatment, secondary stroke prophylaxis and rehabilitation, instead of brain radiation and chemotherapy. Keywords: physical examination, homonymous hemianopsia, stroke, esophageal tumor